2015
DOI: 10.5430/afr.v4n1p164
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Efficiency and Profitability of Listed Banks in Ghana

Abstract: The Ghanaian banking industry has had both good and bad times as far as profit is concerned. However, the industry remains good, as evidened from the rising number of other banks from the continent to either merge with the indigenous banks or take over the operation of some of the local banks. In this view this; the study assessed the efficiency and profitability of banks operating in Ghana by using listed banks between the years 2006 to 2011. This quantitative study employed panel data approach using regressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
0
5
0
1
Order By: Relevance
“…Menurut Buchory (2015) bahwa jika kredit gagal, maka kemampuan bank untuk memberikan pinjaman baru akan dibatasi. Peningkatan risiko kredit biasanya menunjukkan bahwa profitabilitas bank menurut Mawutor & Fred (2015), NPL yang tinggi mengindikasikan bahwa pengelolaan kredit pada bank tidak optimal yang mengakibatkan risiko kredit yang dialami oleh bank tersebut akan menjadi tinggi. Semakin tinggi rasio dari NPL, maka akan menyebabkan semakin buruk pula kualitas kredit bank suatu bank yang artinya jumlah kredit bermasalah semakin besar, sehingga kemungkinan suatu bank dalam kondisi bermasalah akan semakin besar dan dapat mengakibatkan turunnya ROA suatu bank.…”
Section: Gambar 1rata-rata Return On Assets Bank Umum Periode 2013-2015unclassified
“…Menurut Buchory (2015) bahwa jika kredit gagal, maka kemampuan bank untuk memberikan pinjaman baru akan dibatasi. Peningkatan risiko kredit biasanya menunjukkan bahwa profitabilitas bank menurut Mawutor & Fred (2015), NPL yang tinggi mengindikasikan bahwa pengelolaan kredit pada bank tidak optimal yang mengakibatkan risiko kredit yang dialami oleh bank tersebut akan menjadi tinggi. Semakin tinggi rasio dari NPL, maka akan menyebabkan semakin buruk pula kualitas kredit bank suatu bank yang artinya jumlah kredit bermasalah semakin besar, sehingga kemungkinan suatu bank dalam kondisi bermasalah akan semakin besar dan dapat mengakibatkan turunnya ROA suatu bank.…”
Section: Gambar 1rata-rata Return On Assets Bank Umum Periode 2013-2015unclassified
“…Information technology is an essential instrument of competition used by business concern and banks seeking to stay dominant and achieve competitive superiority over others (Roy, 2018). This implies that banks and firms will continue to embrace technological innovations as it improve both product and service quality (Mawutor, 2014;Nworuh & Ahaiwe, 2003). Sharing similar thought, Adewuyi, (2011) opined that banks often invest funds in emerging technologies as a strategic and tactical channel for staying competitive.…”
Section: Background To the Studymentioning
confidence: 99%
“…Asia and Ratan (2019) investigated the relationship between corporate governance and non-performing loans of listed commercial banks in Bangladesh and found that corporate governance had a significant positive effect on non-performing loans of the sampled listed banks in Bangladesh. Mawutor and Awah (2014) reported that liquidity and bank size had insignificant negative effect on return on assets, while credit risk, leverage and productivity also had a negative but significant effect on return on assets of the listed banks in Ghana. In Taiwan, Chen and Pan (2012) concluded that credit risk efficiency had a weak but insignificant correlation with shareholders' wealth of the sampled banks for the period under consideration.…”
Section: Review Of Extant Literaturementioning
confidence: 99%